2014
DOI: 10.2166/wcc.2014.027
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for risk assessment of flash flood events due to climate and land-use changes: application to the Llobregat basin

Abstract: Global change, including climate, land-use and socio-economic changes, is expected to increase the stress on the entire water cycle. In the Mediterranean region, extreme events are likely to increase due to climate change. This work, framed in the EC Seventh Framework Programme project IMPRINTS, presents a methodology to obtain future flood risk maps using climate and land-use scenarios, identifying the new potential risk zones. The implementation of this methodology is applied to the Llobregat river basin cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The scope of study includes watersheds (Nuanchan et al 2015;, deserts (Duan et al 2012), wetlands (Gong et al 2011), etc., delimited by ecological scope, as well as provinces and municipalities delimited by administrative or territorial scope, and countries (Zhao et al 2007;Cirelli & Vineri 2014;Burgalassi & Luzzati 2015;Li & Qi 2019). The research content extends to urban structure (Yang et al 2017), urban flooding (Velasco et al 2014;Philip et al 2021), low-carbon cities (Piao et al 2009;Li & Zhou 2021), and urban climate (Suder & Szymanowski 2014). Urban expansion, a process of human-driven disturbance, has an increasingly significant impact on regional landscape patterns and ecological functions and processes (Zeng & Jiang 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The scope of study includes watersheds (Nuanchan et al 2015;, deserts (Duan et al 2012), wetlands (Gong et al 2011), etc., delimited by ecological scope, as well as provinces and municipalities delimited by administrative or territorial scope, and countries (Zhao et al 2007;Cirelli & Vineri 2014;Burgalassi & Luzzati 2015;Li & Qi 2019). The research content extends to urban structure (Yang et al 2017), urban flooding (Velasco et al 2014;Philip et al 2021), low-carbon cities (Piao et al 2009;Li & Zhou 2021), and urban climate (Suder & Szymanowski 2014). Urban expansion, a process of human-driven disturbance, has an increasingly significant impact on regional landscape patterns and ecological functions and processes (Zeng & Jiang 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional approaches for modeling flood risk are mostly dependent on the flood water depth to estimate the associated damage (Aerts et al 2014, Velasco et al 2014. Several recent studies have shown that considering multivariate data will improve the damage estimates (Wagenaar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Essential for the long-term sustainable management of watersheds is the need to compare the influences of climate and landuse management factors in concert (Jones, 2011). Because of this recognition, more researchers are now undertaking studies that specifically focus on the combined impacts of future climate and landuse changes on water resources (Velasco et al, 2014;Tong et al, 2016). And some of this work is being undertaken in Canada (Novotna et al, 2014;El-Khoury et al, 2015), as well as the north-east bioregion of New England states and the Atlantic Canadian provinces (Talib & Randhir, 2017;.…”
Section: Introductionmentioning
confidence: 99%